Immunolocalization of hormones involved in male gestation in the seahorse, Hippocampus barbouri Jordan and Richardson 1908 - Oconer, E. P.; Herrera, A. A.; Amparado, E. A.; Wetzel, J. T.; De La Paz, R. M. (2003)
Seahorses are teleosts that have evolved a brood pouch analogous to the mammalian uterus. Attempts to breed the fish in captivity - a prerequisite for aquaculture and conservation of this species - are hampered by many unanswered questions regarding its general reproductive biology, especially its gestation. To determine if the hormones secreted by gestating female mammals are the same hormones involved in the unique pattern of male gestation in the seahorse (Hippocampus barbouri Jordan and Richardson 1908), the site of synthesis of hormones apparently involved in male gestation was localized by immunohistochemistry, and the presence of 3 ẞ-hydroxysteroid dehydrogenase was investigated through enzyme histochemical analysis. Ultrastructure of the brood epithelium was further analyzed using transmission electron microscope. Results showed that both progesterone and estradiol are involved in gestation in the male seahorse. Synthesis of estrogen and progesterone was observed in the testis, brood pouch and interrenal tissues of gravid seahorse. Increase in the number and size of mitochondria was noted in gravid pouch.
Keywords: Sea horses; Reproductive organs